Disaggregated mortality from gastrointestinal cancers in Asian Americans: Analysis of United States death records. Issue 12 (9th February 2021) - Huang, Robert J.; Sharp, Nora; Talamoa, Ruth; Kapphahn, Kristopher; Sathye, Vedant; Lin, Bryant; Srinivasan, Malathi; Palaniappan, Latha P.
Abstract: Asian Americans (AAs) are heterogeneous, and aggregation of diverse AA populations in national reporting may mask high‐risk groups. Gastrointestinal (GI) cancers constitute one‐third of global cancer mortality, and an improved understanding of GI cancer mortality by disaggregated AA subgroups may inform future primary and secondary prevention strategies. Using national mortality records from the United States from 2003 to 2017, we report age‐standardized mortality rates, standardized mortality ratios and annual percent change trends from GI cancers (esophageal, gastric, colorectal, liver and pancreatic) for the six largest AA subgroups (Asian Indians, Chinese, Filipinos, Japanese, Koreans and Vietnamese). Non‐Hispanic Whites (NHWs) are used as the reference population. We found that mortality from GI cancers demonstrated nearly 3‐fold difference between the highest (Koreans, 61 per 100 000 person‐years) and lowest (Asian Indians, 21 per 100 000 person‐years) subgroups. The distribution of GI cancer mortality demonstrates high variability between subgroups, with Korean Americans demonstrating high mortality from gastric cancer (16 per 100 000), and Vietnamese Americans demonstrating high mortality from liver cancer (19 per 100 000). Divergent temporal trends emerged, such as increasing liver cancer burden in Vietnamese Americans, which exacerbated existing mortality differences. There exist striking differences in the mortality burden of GI cancers by disaggregated AA subgroups. These data highlight the need for disaggregated data reporting, and the importance of race‐specific and personalized strategies of screening and prevention. Abstract : What's new? Aggregating cancer data from all Asian‐Americans into a single statistic may mask the presence of high risk groups within this population. Here, the authors report mortality rates of gastrointestinal (GI) cancers broken down by ethnicity for the six largest Asian American subgroups in the US: Indians, Chinese, Filipinos, Japanese, Koreans, and Vietnamese. Using death records from 2003‐2017, they analyzed trends in mortality from esophageal, gastric, colorectal, liver, and pancreatic cancers. They found considerable variation in which cancers occurred in each subgroup. In addition, overall mortality was 3‐fold higher in the highest category, Korean‐Americans, than the lowest, Indian‐Americans.